Curcumin derivatives and Aβ-fibrillar aggregates: An interactions' study for diagnostic/therapeutic purposes in neurodegenerative diseases. Issue 14 (7th August 2018) - Orteca, Giulia; Tavanti, Francesco; Bednarikova, Zuzana; Gazova, Zuzana; Rigillo, Giovanna; Imbriano, Carol; Basile, Valentina; Asti, Mattia; Rigamonti, Luca; Saladini, Monica; Ferrari, Erika; Menziani, Maria Cristina
Graphical abstract: Abstract: Several neurodegenerative diseases, like Alzheimer's (AD), are characterized by amyloid fibrillar deposition of misfolded proteins, and this feature can be exploited for both diagnosis and therapy design. In this paper, structural modifications of curcumin scaffold were examined in order to improve its bioavailability and stability in physiological conditions, as well as its ability to interfere with β-amyloid fibrils and aggregates. The acid-base behaviour of curcumin derivatives, their pharmacokinetic stability in physiological conditions, and in vitro ability to interfere with Aβ fibrils at different incubation time were investigated. The mechanisms governing these phenomena have been studied at atomic level by means of molecular docking and dynamic simulations. Finally, biological activity of selected curcuminoids has been investigated in vitro to evaluate their safety and efficiency in oxidative stress protection on hippocampal HT-22 mouse cells. Two aromatic rings, π-conjugated structure and H-donor/acceptor substituents on the aromatic rings showed to be the sine qua non structural features to provide interaction and disaggregation activity even at very low incubation time (2h). Computational simulations proved that upon binding the ligands modify the conformational dynamics and/or interact with the amyloidogenic region of the protofibril facilitating disaggregation. Significantly, in vitro results on hippocampal cells pointed out protection against glutamate toxicity and safety when administered at low concentrations (1 μM). On the overall, in view of its higher stability in physiological conditions with respect to curcumin, of his rapid binding to fibrillar aggregates and strong depolymerizing activity, phtalimmide derivative K2F21 appeared a good candidate for both AD diagnostic and therapeutic purposes.